(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2016)
The discussion of God’s covenant in Hebrews 8 forms part of the section on the superiority of the highpriesthood of Christ to the Levitical priesthood, which begins in 4:14 and concludes in 10:18. As the argument develops, it becomes increasingly clear that there are not only aspects of discontinuity, but also of continuity between the old system set up under Moses and the new one established in Christ. This also applies to the old and new covenant, as described in chapter 8:6-13. The purpose of this article is to investigate God’s covenant within the context of chapter 8. In the first part the distinction between continuity and discontinuity is described from an epistemological perspective. The second part deals with the way in which the author of the letter uses it in describing the covenant of God in the old and new dispensations. It is argued that the theme of God’s covenant entails an implicit awareness of the foundational relationship between continuity (constancy) and discontinuity (change), which enables him to explain the identity of the covenant in this specific chapter. The article also pays attention to several rhetorical means used by the author to persuade his readers to his point of view, thereby encouraging them to persevere on their pilgrimage to the heavenly kingdom that Christ as high priest has prepared for them.